Evaluasi Pelatihan Kepemimpinan Pada Karyawan PT Brantas Energi - Berlian, Mochammad Bayu; Laksono, Riyadi Dwi; Wahyuni, Vivi; Rusliana, Iu (Universitas Islam Kadiri, 2023)
The purpose of this research is to find out how effective the leadership training with the theme